2003
DOI: 10.1021/ie0207111
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Carbonation−Calcination Reactions of Ca-Based Sorbents for Efficient CO2 Sorption at Elevated Temperatures and Pressures

Abstract: In an effort to develop a novel hydrogen production process in which coal is gasified with highpressure steam in the presence of CO 2 sorbents, the fundamental CO 2 sorption characteristics of Ca-based sorbents during repetitive carbonation-calcination reactions at different pressures were investigated using a conventional TG/DTA analyzer and a laboratory-scale horizontaltube reactor. The results revealed that, as a result of sintering and crystal growth, Ca-based sorbents were significantly deactivated by hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 17 publications
2
62
0
5
Order By: Relevance
“…It can be seen that the carbonations and calcinations are reversible in practice since, after the first and second carbonations, there is only calcium carbonate and after calcinations there is mostly calcium oxide. Kuramoto et al (2003) also reported that the sorbent regenerates, maintaining the CO2 capture capacities of this type of mineral over calcination-hydration-carbonation cycles. The authors compared the results with and without intermediate hydration of CaO, suggesting that the hydration treatment provides the durability of the sorbents in repetitive CO2 sorption.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…It can be seen that the carbonations and calcinations are reversible in practice since, after the first and second carbonations, there is only calcium carbonate and after calcinations there is mostly calcium oxide. Kuramoto et al (2003) also reported that the sorbent regenerates, maintaining the CO2 capture capacities of this type of mineral over calcination-hydration-carbonation cycles. The authors compared the results with and without intermediate hydration of CaO, suggesting that the hydration treatment provides the durability of the sorbents in repetitive CO2 sorption.…”
Section: Resultsmentioning
confidence: 81%
“…Previous studies investigating carbonation of Ca(OH)2 and carbonation of CaO show that Ca(OH)2 reaches a higher conversion than CaO (Nikulshina et al, 2007;Kuramoto et al, 2003), whereas the carbonation of CaO is initially chemically controlled and then becomes controlled by diffusion, while the carbonation of Ca(OH)2 at high temperatures (up to 400 °C) is all chemically controlled (Nikulshina et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, at 225 o C Ca(OH) 2 [11] and CsOH layers were formed on the sorbent's surface due to high water adsorption, namely 27 wt% H 2 O/mass of sorbent. However, with increasing sorption temperature a considerable decrease of the water adsorption was observed.…”
Section: Effect Of Temperature On H 2 O Adsorptionmentioning
confidence: 99%